Rethinking Place Branding Comprehensive Brand Development for Cities and Regions - Kavaratzis, Mihalis; Warnaby, Gary.; Ashworth, Gregory J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
As Place Branding has become a widely established but contested practice, there is a dire need to rethink its theoretical foundations and its contribution to development and to re-assert its future. This important new book advances understanding of place branding through its holistic, critical and evidence-based approach. Contributions by world-leading specialists explore a series of crucially significant issues and demonstrate how place branding will contribute more to cultural, economic and social development in the future. The theoretical analysis and illustrative practical examples in combination with the accessible style make the book an indispensable reading for anyone involved in the field.
The Need to Rethink Place Branding -- Rethinking the Place Branding Construct -- Rethinking the Place Product from the Perspective of the Service-Dominant Logic of Marketing -- Rethinking Sense of Place: Sense of One and Sense of Many -- Rethinking Place Identities -- Rethinking Virtual and Online Place Branding -- Rethinking Strategic Place Branding in the Digital Age -- Rethinking Place Branding from a Practice Perspective: Working with Stakeholders -- Rethinking the Roles of Culture in Place Branding -- Rethinking Place Branding and Place Making Through Creative and Cultural Quarters -- Rethinking Place Brand Communication: From Product-Oriented Monologue to Consumer-Engaging Dialogue -- Rethinking the Visual Communication of the Place Brand: A Contemporary Role for Chorography? -- Rethinking Place Branding and the "Other" Senses -- Rethinking the Measurement of Place Brands -- Rethinking Brand Equity: Possibilities and Challenges of Application to Places -- Sketching Futures for Place Branding.
Keywords: Economics; Regional planning; Architecture; Regional economics; Marketing; Economics/Management Science; Marketing; Regional/Spatial Science; Landscape/Regional and Urban Planning; Cities, Countries, Regions